2021
DOI: 10.7717/peerj-cs.349
|View full text |Cite
|
Sign up to set email alerts
|

ADID-UNET—a segmentation model for COVID-19 infection from lung CT scans

Abstract: Currently, the new coronavirus disease (COVID-19) is one of the biggest health crises threatening the world. Automatic detection from computed tomography (CT) scans is a classic method to detect lung infection, but it faces problems such as high variations in intensity, indistinct edges near lung infected region and noise due to data acquisition process. Therefore, this article proposes a new COVID-19 pulmonary infection segmentation depth network referred as the Attention Gate-Dense Network- Improved Dilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Again, similar to our study, in a study using the U-net algorithm, CT images of COVID-19 patients were evaluated and the values for the sensitivity, precision, and F1-score were calculated as 0.8, 0.82 and 0.81, respectively. In the same study, it was shown that the results could be further improved by adding various modules to the U-net algorithm [35]. In another study using a fully connected network, which is a somewhat similar method, photographs of skin lesions were evaluated, and the F1-score and sensitivity values were found to be 0.912 and 0.918, respectively [36].…”
Section: Discussionmentioning
confidence: 95%
“…Again, similar to our study, in a study using the U-net algorithm, CT images of COVID-19 patients were evaluated and the values for the sensitivity, precision, and F1-score were calculated as 0.8, 0.82 and 0.81, respectively. In the same study, it was shown that the results could be further improved by adding various modules to the U-net algorithm [35]. In another study using a fully connected network, which is a somewhat similar method, photographs of skin lesions were evaluated, and the F1-score and sensitivity values were found to be 0.912 and 0.918, respectively [36].…”
Section: Discussionmentioning
confidence: 95%
“…Before concatenation, the attention mechanism is allowed in the segmentation network. The attention mechanism in [49] , [50] , [51] combines linear transformation and non-linear activation function. The residual attention [52] extracts local and non-local features.…”
Section: Methodologiesmentioning
confidence: 99%
“…However, the method is conceived to segment the single class and on a small dataset. A recent approach (Raj et al, 2021) leverages a depth network, namely ADID-UNET, to enhance the COVID-19 segmentation performance on CT images. The proposed method is evaluated on public datasets and achieved a 97.01% accuracy, a precision of 87.76%, and an F 1 score of 82.00%.…”
Section: Applications Of Deep Learning In Healthcarementioning
confidence: 99%
“…Table 9 reveals the the compared performance of the proposed approach with the state-ofthe-art methods including SegNet (Budak et al, 2021), Unet (Zhou, Canu & Ruan, 2020) with attention mechanism, and ADID-UNET (Raj et al, 2021). We compared our configurations with the others on Dice, Sensitivity, and Precision values.…”
Section: Covid-19 Segmentationmentioning
confidence: 99%
See 1 more Smart Citation